An augmented approach to support collaborative distance learning of Unified Modeling Language - SIAU, Keng (Institutional Knowledge at Singapore Management University, 2007)
Teaching in the classroom faces many challenges of providing a collaborative, interactive environment that effectively facilitates students’ learning. The challenges increase when the physical classroom converts into a virtual classroom. This difficulty is further exacerbated when the course is diagramming intensive, practice-oriented, and hands-on in nature. Technology has been sought after to help with these challenges. Web Conferencing software, when compared to Web Broadcasting software, can facilitate real-time interaction and collaboration in a distance learning context. For courses that are diagramming intensive and practice-oriented, Tablet PCs, when compared to desktop PCs, can support drawing and diagramming because of the ability to write, sketch, draw, and annotate using electronic ink and drawing tools. These capabilities, when used with Web Conferencing software, add new dimensions to facilitating interaction and collaboration in a virtual classroom. In this research, we examine the use of advanced technologies, specifically Tablet PCs and Web Conferencing software, to support collaborative distance learning of a diagramming intensive and hands-on course – Object-Oriented Systems Analysis and Design (OSAD). The de facto Object-Oriented modeling language, Unified Modeling Language, will be taught in the OSAD course. Our proposed experimental study will examine three conditions or ways of teaching OSAD in a distributed or distance learning context: (i) desktop PCs with Web Broadcasting; (ii) desktop PCs with Web Conferencing; and (iii) Tablet PCs with Web Conferencing. Theories of Media Richness and Media Synchronicity serve as the theoretical foundation for the research.